Shortcomings in the classification of public science and technology organizations in implementing the autonomy and self-responsibility mechanism in Vietnam - Nguyen Thi Minh Hanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
In Vietnam, the implementation of the autonomy and self-responsibility mechanism for public science and technology organizations has gone through two important milestones: (1) Period 2005-2015, implemented according to regulations in Decree No.115/2005/ND-CP dated September 5, 2005 regulating the autonomy and self-responsibility mechanism of public science and technology organizations; and (2) Period 2016-2022, implemented according to the provisions of Decree Decree No.54/2016/ND-CP dated June 14, 2016 regulating the autonomy mechanism of public science and technology organizations. This article will focus on analyzing some shortcomings in classifying public science and technology organizations in implementing the autonomy and self-responsibility mechanism according to Decree No. 115/2005/ND-CP and Decree No.54/ 2016/ND-CP. Code: 24062601